Frictional Characteristic Curves of Ground Surfaces in Lubricated Sliding - Gopakumar Parameswaran; Vikram Jayaram; Satish V. Kailas (Lubricants, 2023)
The key objective of the presented study was to use a commercially feasible and scalable approach to modifying surfaces to reduce friction. In an industrial setting, surface grinding is commercially viable and scalable as compared to other surface modifying processes like laser surface texturing, plasma, or ion beam milling. Frictional force plots are generated from the lubricated contact interface between a flat-faced aluminum pin and a reciprocating stainless steel countersurface driven by a scotch yoke follower mechanism. Using a surface grinder and selecting coated abrasive sheets, different stainless steel surface specimens, classified as P320, P1200, and mirror were prepared and tested in this study. The frictional force encountered by the pin was recorded using a data acquisition system at discrete intervals in the reciprocating path and averaged along the sliding cycles. The shape of the frictional force plots thus generated were found to be different from each other. Various mechanisms of friction prevalent at the contact were presumed to influence the shape of these frictional plots. These mechanisms were tested by varying the sliding speeds, lubricating oil viscosities, and using tribofilm-forming additives. We used Group 1 base oil of two different viscosities in our tests. At lower speeds, the frictional force plot for the mirror-finished surface seemed to conform to the Stribeck curve, while in the same scale of reference, the P1200 surface had a force plot that was nearly flat and of very low magnitude. At the contact interface, there seemed to be a fine balance existing between adhesion and abrasion phenomena, while oil retention was promoted to achieve extremely low sliding friction.